Chemical Properties of Salacca Seed Biochar Under Low Temperature of Pyrolysis (Research and Social Study Institute, 2022)
Salak or Salacca fruit is a seasonal fruit; in some cases, this fruit easy rotten due to a lack of handling during the harvesting process or wet or humid storage. This condition will promote much waste because the fruit cannot be eaten. To minimize the waste, the seed of salak fruit can be converted to biochar. This study aimed to determine the chemical properties of biochar derived from the seeds of salacca (Salacca zalacca). The biochar is produced by burning the seeds using a furnace with a temperature of 350°C and 450°C, then ground and sieved with a size of 355 micrometers carried out at the Research Center for Limnology and Water Resources. Chemical property analysis using X-Ray Fluorescence Spectrometer (XRF) at the Lampung Advanced Characterization Laboratory- BRIN. The results show that most composition is Potassium (K). Potassium (67-70%) is the most abundant element in Salacca seed biochar, followed by chlorine. Biochar burned at 350 °C has a potassium content of 70.25%, while biochar burned at 450 °C has a potassium content of 67.86%. Biochar burned at 350 °C has a chlorine content of 25.35%, while biochar burned at 450 °C has a chlorine content of 24.66%. The percentage of potassium and chlorine decreases as the temperature rises. Furthermore, the phosphorus (P) and calcium (Ca) content of biochar appear at biochar burned at 450 °C.